Impact of Metabolic Syndrome and Its Components on Clinical Severity and Long-Term Prognosis in Patients With Premature Myocardial Infarction - Gao, Jing; Wang, Yuan; Yang, Ya-Nan; Wu, Xiao-Yuan; Cui, Yan; Zou, Zhong-He; Cui, Zhuang; Liu, Yin (Frontiers in Endocrinology, 2022)
Background: The effects of metabolic syndrome (MS) on premature myocardial infarction (PMI) are not clear to date. This study aimed to investigate the impact of MS and its components on clinical severity and long-term prognosis in patients with PMI. Methods: We enrolled 772 patients aged ≤45 years old who were diagnosed with acute myocardial infarction (AMI) at our hospital consecutively between 2015 and 2020. The patients were divided into an MS group and non-MS group. The parameters of clinical severity were compared using regression analysis. Patients were followed for median of 42 months for major adverse cardiovascular events (MACE). Results：Hyperglycemia was associated with multi-vessel disease[odds ratio(OR)=1.700, 95% confidence interval (CI)=1.172-2.464, P=0.005] and Syntax score ≥33(OR=2.736, 95% CI=1.241-6.032, P=0.013).Increased MACE were observed in the MS group(17.9% vs 10.3%, P=0.004).The Kaplan-Meier curve also showed significant differences (P< 0.001). MS was an independent risk factor for MACE. Of each component of MS, BMI ≥28 kg/m2 (hazard ratio [HR]=2.02247, 95% CI =1.21329-3.369410, P=0.0076] and hyperglycemia (HR=2.90411, 95% CI=1.84750-4.56780, P<0.001) were independent risk factors for MACE. Conclusions: In patients with PMI, 1) hyperglycemia usually indicates more severe lesions; 2) MS as a whole was an independent risk factor for MACE; 3) BMI ≥28.0 kg/m2 and hyperglycemia were associated with MACE. Key words：Metabolic syndrome, Premature myocardial infarction, Clinical severity, Long-term prognosis, MACE